PENGEMBANGAN POCKET BOOK PADA MATERI IKATAN ION BERBASIS PROBLEM BASED LEARNING (PBL) BERORIENTASI KEMAMPUAN BERPIKIR KRITIS SISWA - Ulqairi Putri Suita; Epinur; Afrida; Yusnaidar; Firdiawan Ekaputra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study developed a Problem-Based Learning (PBL)-based pocket book on ionic bonding that is oriented toward students’ critical thinking skills. Twenty-first-century learning requires students to possess the 4C skills, one of which is critical thinking. This PBL-based pocket book was developed to help students learn independently, understand the concept of ionic bonding more easily, and facilitate the development of critical thinking skills. This study aims to examine the development process, the level of feasibility, and student responses to the PBL-based pocket book on ionic bonding designed to foster students’ critical thinking skills. This study employs a research and development (R&D) methodology using the Lee & Owens development model, which includes the stages of analysis, design, development, implementation, and evaluation. The research instruments used consist of interview sheets and questionnaires. The resulting product was validated by media experts and subject matter experts and evaluated by teachers. Subsequently, the product was pilot-tested with students through one-on-one and small-group trials. The data analysis techniques used were qualitative data analysis (comments and suggestions) and quantitative data analysis (assessment scores and percentages). The results of this study showed that the content was conceptually valid (highly valid) based on subject matter expert validation, with an average score of 4.65, and media expert validation, with an average score of 4.45. Evaluations by chemistry teachers yielded an average score of 4.42, meeting the “highly feasible” criterion. Additionally, the one-on-one pilot test achieved a success rate of 90.22% (very good), and the small-group pilot test achieved a success rate of 89.20% (very good). Based on the development process and research results, it can be concluded that the Problem-Based Learning (PBL)-based pocket book on ionic bonds—designed to foster students’ critical thinking skills—is deemed suitable and very good for proceeding to the field-test phase as a learning resource that can help students improve their understanding of chemistry in school.